Neutron background environment measured by the Mars Science Laboratory's Dynamic Albedo of Neutrons instrument during the first 100 sols. Issue 11 (25th November 2013) - Jun, I.; Mitrofanov, I.; Litvak, M. L.; Sanin, A. B.; Kim, W.; Behar, A.; Boynton, W. V.; DeFlores, L.; Fedosov, F.; Golovin, D.; Hardgrove, C.; Harshman, K.; et al.
Abstract [1] The Dynamic Albedo of Neutrons (DAN) instrument on board Mars Science Laboratory has been operating successfully since the landing and has been making measurements regularly along Curiosity's traverse at the surface. DAN measures thermal (E < 0.4 eV) and epithermal neutrons (0.4 eV < E < 1 keV) while operating in two different modes: active and passive. The active mode uses a pulsed neutron generator (PNG) to study the geological characteristics of the subsurface. In the passive mode, DAN measures the background neutron environment. This paper presents results of measurements in the passive mode from landing through to sol 100 and provides an interpretation of the data based on extensive Monte Carlo simulations. The main observations are summarized as follows: (1) the thermal neutron counts vary strongly along the rover traverse while the epithermal counts do not show much variation; (2) the neutrons from the Multi‐Mission Radioisotope Thermoelectric Generator (MMRTG) are a larger contributor to the DAN passive data than the Galactic Cosmic Ray (GCR)‐induced neutrons; (3) for the MMRTG neutrons, both the thermal and the epithermal counts increase as a function of the subsurface water content; (4) on the other hand, for the GCR‐induced neutrons, the thermal counts increase but the epithermal counts decrease as a function of the subsurface water content; and (5) relative contributions by the MMRTG and GCR to the DAN thermal neutron counts at the Rocknest site, where the rover was stationed from sol 59 to sol 100, are estimated to be 60% and 40%, respectively.